Revisiting ENSO/Indian Ocean Dipole phase relationships. Issue 5 (13th March 2017) - Stuecker, Malte F.; Timmermann, Axel; Jin, Fei‐Fei; Chikamoto, Yoshimitsu; Zhang, Wenjun; Wittenberg, Andrew T.; Widiasih, Esther; Zhao, Sen
Abstract: Here we show that the characteristics of the Indian Ocean Dipole (IOD), such as its power spectrum and phase relationship with the El Niño–Southern Oscillation (ENSO), can be succinctly explained by ENSO combination mode (C‐mode) wind and heat flux forcing together with a seasonal modulation of the air/sea coupled Indian Ocean (IO) Bjerknes feedback. This model explains the observed high‐frequency near‐annual IOD variability in terms of deterministic ENSO/annual cycle interactions. ENSO‐independent IOD events can be understood as a seasonally modulated ocean response to white noise atmospheric forcing. Under this new physical null hypothesis framework, IOD predictability is determined by both ENSO predictability and the ENSO signal‐to‐noise ratio. We further emphasize that lead/lag correlations between different climate variables are easily misinterpreted when not accounting properly for the seasonal modulation of the underlying climate phenomena. Key Points: A physical null hypothesis for the IOD is presented A simple low‐order model captures the IOD spectrum and ENSO/IOD phase relationship IOD predictability is determined by ENSO predictability and ENSO signal‐to‐noise ratio